Analysis of team sports results based on the European basketball men’s championships - Pluta, Beata; Andrzejewski, Marcin (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The paper is a univariate study examining the performance in professional basketball. The authors did not include the influence of situational variables that affects the game dynamics thus the aim of the conducted study was the sole analysis of the point results obtained from selected basketball games. Aim of Study. The main topic of the study was the analysis of the impact of rule modifications on match results in men’s professional basketball. Material and Methods. The research material consisted of numerical data on results of all matches played at men’s European Basketball Championships between 1935 and 2015. All statistical calculations were carried out using the STATISTICA software package. Six main basketball rule modifications which directly affected the course of matches were identified in chronological order. Results. The results of the study showed that subsequent changes of basketball rules not always directly affected a match score. The number of scored points and allowed points following each consecutive rule modification since 1956 changed significantly. The greatest changes in match scores were noted after having introduced the modifications of basketball rules from 1956 and 1984. Conclusions. Rule modification involves processes that seek change in the game conditions, thus modifications in basketball should also be validated after following a reflective process. The main purposes of any future rule modifications in basketball should be to improve players performance, respond more efficiently to commercial pressures and interests, and finally attract more prospective players.
Keywords: rules modification; sports tournament; performance analysis; team sports